Factores que inciden en el desempeño eficiente de una oficina de transferencia de resultados de investigación (OTRI): Caso cientech (2016)
Due to the summit of the transfer of knowledge like source of economic development for the regions and countries, the TTO´s are raised as intermediary structures of out-standing importance inside the Regional Systems of Science, Technology and Innovation, which make possible the transfer of research results to the business sector and the community in general. In the Latin-American context, the emergence of the TTO obeys a very recent dynamics, where his possibilities of action have met limited for determining economic, social and cultural. This fact reveals the need to go deeply into those more relevant factors on which these could establish the bases for the achievement of a few suitable levels of performance from his early phases of operation. Based on the methodology of the case study will examine these factors in CienTech, an TTO of new creation in the Department of Atlántico - Colombia, being the result a synthesis of the most relevant factors that affect in the efficient performance of the TTO of new creation.